Type-2 diabetes mellitus and the frequency of the G22A polymorphism of the adenosine deaminase gene in a mixed population in Brazil - Bonini Domingos, Ana Carolina [UNESP]; Iacida, Edi Carlos [UNESP]; Oliveira, Rafael Monteiro de [UNESP]; Bonini-Domingos, Claudia Regina [UNESP]; Brandao de Mattos, Cinara de Cassia; Mattos, Luiz Carlos de (Oxford University Press, 2014)
Most individuals diagnosed with diabetes mellitus (about 90%) have type 2 disease (T2DM). T2DM is associated with a high genetic predisposition and is characterized by changes in the secretion and action of insulin. There have been reports of increased activity of the adenosine deaminase enzyme in individuals with coronary heart disease and DM.We evaluated 162 patients with T2DM and 160 individuals without the disease. Additionally, a subgroup of 81 individuals at higher risk of developing cardiovascular diseases was formed from the group of patients with diabetes on the basis of their serum levels of high-density lipoprotein cholesterol (HDLc), low-density lipoprotein cholesterol (LDLc) and triglycerides. PCR-RFLP was performed to analyze the TaqI polymorphism G428A of the ADA gene; this technique identifies the ADA*01 and ADA*02 alleles.Genotype frequencies were calculated for three patient groups, as follows. Patients with diabetes: ADA*01;*01 (142/159, 89.3%), ADA*01;*02 (16/159, 10.1%) and ADA*02;*02 (1/159, 0.6%); control group: ADA*01;*01 (146/160, 91.3%), ADA*01;*02 (12/160, 7.5%) and ADA*02;*02 (2/160, 1.3%); patients at risk of cardiovascular disease: ADA*01;*01 (71/78, 91.0%), ADA*01;*02 (7/78, 9.0%) and ADA*02;*02 (0/78, 0.0%).No statistically significant differences between the groups were observed in the genotype and allele frequencies. However, this fact does not rule out the need for further studies on the frequencies of this polymorphism in the Brazilian population, on any association with ADA enzyme activity, and on other risk factors that can affect the quality of life of Brazilian patients with T2DM.
Keywords: Adenosine deaminase enzyme polymorphism; Risk of cardiovascular disease; Type-2 diabetes mellitus